The effects of particle size and dried whey level in barley diets for starter-pigs - Goodband, Robert D.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred and thirty-six weanling pigs were utilized in two, 3 X 2 factorial design experiments to determine the effects of whey level (0, 10 or 20%) and particle size (1/8 or 3/16-in screen size) in barley diets on starter-pig performance. Grinding barley through a 1/8-in screen decreased the mean particle size of the diet compared to diets made up of barley ground through a 3/16-in screen. Average daily gain (ADG) and average daily feed intake (ADFI) increased linearly (P<.01) as whey level increased. Pigs fed diets containing 1/8-in ground barley were more efficient (P<.02) than those fed diets containing 3/16-in ground barley. However, pigs fed a 20% dried whey-milo-soybean meal control diet grew faster (P<.05) than those fed any of the barley starter diets. In these experiments, the relative feeding value of 20% dried whey-barley starter diet was 94-97% that of the 20'% dried whey-milo diet. Also, these results indicate that increasing levels of dried whey improves ADG and ADFI of pigs fed barley-based starter diets, and decreasing particle size of the diet improves feed efficiency.
Keywords: Swine; Particle size; Whey; Starter-pigs